The correspondence theory of truth : - Newman, Andrew (Cambridge University Press, 2002)
This work presents a version of the correspondence theory of truth based on Wittgenstein's Tractatus and Russell's theory of truth and discusses related metaphysical issues such as predication, facts, and propositions. Like Russell and one prominent interpretation of the Tractatus, it assumes a realist view of universals and argues that facts as real entities are not needed. It will intrigue teachers and advanced students of philosophy interested in the conception of truth and in the metaphysics related to the correspondence theory of truth.